1999
DOI: 10.1038/20194
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/calmodulin binds to and modulates P/Q-type calcium channels

Abstract: Neurotransmitter release at many central synapses is initiated by an influx of calcium ions through P/Q-type calcium channels, which are densely localized in nerve terminals. Because neurotransmitter release is proportional to the fourth power of calcium concentration, regulation of its entry can profoundly influence neurotransmission. N- and P/Q-type calcium channels are inhibited by G proteins, and recent evidence indicates feedback regulation of P/Q-type channels by calcium. Although calcium-dependent inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
376
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 440 publications
(397 citation statements)
references
References 28 publications
18
376
3
Order By: Relevance
“…As a first step in defining the potentially broader spectrum of functional sequelae, we focused on novel splice variations in the ␣ 1A C-terminal tail, because this region contains critical structural determinants for Ca 2ϩ feedback regulation of corresponding channels. In particular, Ca 2ϩ /CaM binding to an IQ-like binding motif in exon 40 , or possibly to a CBD binding motif in exon 42 (Lee et al, 1999, initiates both channel facilitation and inactivation by Ca 2ϩ . The proximity of these structures to exons 43 and 44 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…As a first step in defining the potentially broader spectrum of functional sequelae, we focused on novel splice variations in the ␣ 1A C-terminal tail, because this region contains critical structural determinants for Ca 2ϩ feedback regulation of corresponding channels. In particular, Ca 2ϩ /CaM binding to an IQ-like binding motif in exon 40 , or possibly to a CBD binding motif in exon 42 (Lee et al, 1999, initiates both channel facilitation and inactivation by Ca 2ϩ . The proximity of these structures to exons 43 and 44 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Dolmetsch et al (2001) found that removal of the CaM-binding "IQ motif" from ␣ 1C produces L-type calcium channels incapable of signaling to CREB, demonstrating an inherent prerequisite within the channel for activation of CRE-dependent transcription. Yet various calcium channel ␣ 1 subunits, not just ␣ 1C , contain similar (or identical) IQ motifs and interact with CaM (Lee et al, 1999;Peterson et al, 1999). Thus, another mechanism must provide L-type calcium channels with a "private line" to the nucleus, allowing only these voltage-gated calcium channels to trigger CREB phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple calcium-sensing proteins, including calmodulin, calcium-binding protein-1, and visinin-like protein-2, can interact with calcium channels and mediate use-dependent changes in presynaptic calcium entry (Lee et al 1999(Lee et al , 2002Peterson et al 1999;Lautermilch et al 2005). Presynaptic recordings from the calyx of Held have shown that prolonged high-frequency stimulation reduces calcium entry ) that can contribute to depression.…”
Section: Inactivation Of Calcium Channels and Other Mechanisms Of Depmentioning
confidence: 99%